Relationship of scrotal circumference to age, body weight and testicular volume of swamp buffalo - AHMED, K (The Indian Journal of Animal Reproduction, 2023)
Scrotal circumference (SC) and testicular volume (TV) of thirty eight swamp buffalo bulls maintained at Livestock Research Station, Assam Agricultural University, Mandira and ranging in age from 12 months to 60 months and weighing 132 kg to 358 kg. Ages and body weight (BW) were recorded for each male at the time of measurement to find out correlation with SC and TV. SC and TV increased linearly and correlated significantly with age and BW (SC vs age: r=0.72, P<0.01; SC vsBW, r = 0.82, p<0.01; TV vs BW: r= 0.78, P<0.01). SC measured from 14.1±0.42 to 22.2±0.54 cm for ages ranging from 12 to 60 months. revealing that testicular size in swamp buffaloes was very much smaller than domestic cattle. The SC norms distributed with age would be useful in the evaluation of swamp buffalo male for breeding soundness.